Real, Juan José: "Treinta años de historia argentina. (Acción política y experiencia histórica)". Ediciones Actuales. Buenos Aires, 1962. 254 pág. - Páramo de Isleño, Martha S. (1963)
Fil: Páramo de Isleño, Martha S..